Sistem Pengetahuan Pengobatan Penyakit Jumplang Tanah pada Etnis - Syarif, Umar; Musa, Dahniar Th.; Batuallo, Ignasia Debbye (Balale' : Jurnal Antropologi, 2023)
This article focuses on the phenomenon of traditional medicine in Madurese society, especially local diseases. The disease, which local people call Jumplang Tanah disease, prefers and trusts traditional medicine carried out by shamans. This article has explained the causes and treatment system for Jumplang Tanah disease and analyzed the beliefs of the Madurese people of Sungai Segak village regarding the treatment of Jumplang Tanah disease. This research uses the Health Belief Model theory with six contracts contained in it, namely perceived Susceptibility, Perceived Severity, Perceived Benefits, Perceived Barriers, Cues to Action, and Health Motivation. The research method used is descriptive qualitative, with data collection techniques obtained through the process of observation, interviews, and documentation. The results of this paper provide an understanding of the knowledge and belief systems of the Sungai Segak village community. This cannot be separated from the knowledge passed down from previous Madurese elders, and its existence is still trusted and maintained by the community to this day.